Physical conditions of soccer players participating in training during the new normal era - Limayyasya, Ghoirumamnun; Atiq, Ahmad; Triansyah, Andika; Haetami, Mimi; Hidasari, Fitri Puspa; Marito, Cristine (MEDIKORA, 2022)
Physical condition is one of the most important things for soccer players. The physical condition should be maintained by soccer players as it is part of the strategy to improve techniques, tactics, or strategies in playing soccer. This study aims to investigate the physical condition of students joining the soccer extracurricular program at 7 State Senior High Schools Pontianak, 8 State Senior High Schools Pontianak, and 9 tate Senior High Schools Pontianak. In collecting the data, the researchers focused on phenomena, conditions, or certain variables, but hypothesis testing was not done in this research. The number of samples in this research is 60. This research made use of the quantitative descriptive analysis method, and a survey as done to collect the data. In order to show the cumulative results of the data analysis, percentages were used to present the soccer player conditions in terms of flexibility, agility, speed, endurance, and strength. The results of this research show that 42% of the soccer players belong to the Excellent and Very Good categories. Meanwhile, 58% of the players belong to the Good, Fair, and Poor categories. Based on the result, it is indicated that the players’ physical conditions need to be improved during this pandemic. It is expected that the results of this research may become a positive input for soccer players and supporters in Pontianak